2013
DOI: 10.1152/ajpendo.00614.2012
|View full text |Cite
|
Sign up to set email alerts
|

The autonomic nervous system regulates postprandial hepatic lipid metabolism

Abstract: Bruinstroop E, la Fleur SE, Ackermans MT, Foppen E, Wortel J, Kooijman S, Berbée JF, Rensen PC, Fliers E, Kalsbeek A. The autonomic nervous system regulates postprandial hepatic lipid metabolism. Am J Physiol Endocrinol Metab 304: E1089 -E1096, 2013. First published March 26, 2013; doi:10.1152/ajpendo.00614.2012The liver is a key organ in controlling glucose and lipid metabolism during feeding and fasting. In addition to hormones and nutrients, inputs from the autonomic nervous system are also involved in fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…A second hypothesis is the effect of denervating the liver. This hypothesis has been studied in animal models, showing that parasympathetic denervation results on changes in diet consumption, hypertriglyceridemia, IR, and hypercholesterolemia …”
Section: Discussionmentioning
confidence: 99%
“…A second hypothesis is the effect of denervating the liver. This hypothesis has been studied in animal models, showing that parasympathetic denervation results on changes in diet consumption, hypertriglyceridemia, IR, and hypercholesterolemia …”
Section: Discussionmentioning
confidence: 99%
“…12 We tested our hypothesis in obese (fa/fa) Zucker rats by measuring plasma TG levels and hepatic VLDL-TG secretion during a timeframe of 6 weeks after a surgical sympathetic or parasympathetic denervation of the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical studies have shown that the sympathetic and parasympathetic connections to the liver originate from different brain regions within the hypothalamus and the brainstem . Within the hypothalamus, the paraventricular, arcuate, and suprachiasmatic nuclei as well as the lateral hypothalamic area (LHA) project and modulate liver metabolism …”
mentioning
confidence: 99%